Bandra-Worli Sea Link facing the Worli Village - Mumbai Archive Project Team (Jio Institute, 2024)
The Bandra-Worli Sea Link faced significant opposition during its planning and construction phases from the fishing community of Worli Koliwada. They expressed concern about the impact Sea Link would have on the marine ecosystem. Despite protests, the Sea Link was completed and has become a symbol of modern Mumbai.